Whale shark tourism at Ningaloo Marine Park: A longitudinal study of wildlife tourism - Jones, Roy; Catlin, James (Elsevier Science Ltd, 2010)
This article demonstrates the changes that occur due to the maturation of a wildlife tourism industry through the application of a Wildlife Tourism Framework. Specifically, in 2005 survey data was collect from participants of whale shark tourism at Ningaloo Marine Park in Western Australia, facilitating a direct comparison with a study conducted a decade earlier. The results conformed with predictions by the Framework, in particular, a shift in the industry towards the mainstream from the periphery. In comparison with the past, whale shark tourism at Ningaloo now attracts more generalist tourists who place different preferences on the whale shark tourism experience. There is now a greater distribution of age groups; less skilled individuals; a higher tolerance to crowding; and a larger focus on the non-wildlife components of the experience. Furthermore, this article, discusses the pertinent management implications associated with this shift.